INVESTIGATING THE NEUROCOGNITIVE AND PSYCHOLOGICAL SEQUELAE OF CHRONIC MIGRAINES. (16th November 2018) - Vitale, G; Tran, V; Lenox, M
Abstract: The objective was to determine 1) if migraines correlate with difficulties (e.g., cognitive, psychological, functional) and 2) most impacted domains. The sample (N=140) consisted of primarily (81.4%) female older adults with a mean age of 68.62 years (SD=10.08) and mean education of 16.31 years (SD=2.38). Exclusion criteria: diagnosis of possible/probable neurocognitive disorder, learning disability or substance abuse. Outcomes included age and education-normed z-scores from a cognitive screening, Clinical Dementia Rating (CDR), Neuropsychiatric Inventory-Questionnaire (NPI-Q), and Geriatric Depression Scale-Short Form (GDS-S). De-identified data were collected from the National Alzheimer's Coordinating Center (NACC) database. All measures from the cognitive screening fell within 1 standard deviation of the average (-1